A survey to assess use patterns and perceptions of efficacy of eczema action plans among pediatric dermatologists. Issue 6 (14th September 2018) - Stringer, Thomas; Yin, H. Shonna; Oza, Vikash S.
Abstract: Eczema action plans (EAPs) are written, customizable documents that guide patients through the self‐management of atopic dermatitis. Here, we distributed a survey regarding the use patterns and perceptions of eczema action plans to 1068 members of the Society for Pediatric Dermatology and received 87 responses. Although a strong majority of respondents endorsed the ability of EAPs to improve adherence (79%) and improve prevention and/or management of flares (70%), reported rates of EAP editing or provision sharply decline from initial to follow‐up visits (61%‐33%). The development of a standardized, low‐literacy web‐based tool could improve the efficacy of EAPs for patients and physicians by improving comprehensibility and retention.